Solid Waste and Climate - Serna Mendoza, Ciro Alfonso (2022)
This paper takes as a reference a discussion about what solid waste means in the field of climate change. The bibliographical analyzes place in the discussion how complex the treatment of this topic is becoming, in practical areas. The present investigation was proposed as a fundamental objective to establish the relationship between solid waste and climate change. This area is of fundamental importance because in practice this relationship is not usually established. On the contrary, what is usually found in the literature are studies that carry out isolated analyses. For the development of compliance, the main objective was carried out a review of secondary sources, from different databases, where a profuse literature was found on the subject under study. When reviewing the literature, it is found that solid waste has been producing many pollutants, ranging from air pollution to affecting human health. The foregoing allowed us to conclude that it is necessary to establish public policies that allow working in the territories on the problems related to the mismanagement that is given to solid waste.